2020
DOI: 10.1111/fwb.13595
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of phenotypic plasticity in the response of unionid mussels to turbidity

Abstract: Unionid mussels are among the most imperilled freshwater taxa globally (Lopes-Lima et al., 2017). Their populations have been threatened by factors including over-exploitation (e.g. Strayer et al., 2004), invasive species (e.g. Ferreira-Rodríguez, Sousa, &

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Environmental factors other than salinity may have shaped the colonization of clams during dispersal. High turbidity has the potential for decreased feeding, reduced reproduction and even to reduce shellfish survival (Avelar et al, 2014; Tuttle‐Raycraft & Ackerman, 2020; Wilber & Clarke, 2001). Besides, as filter‐feeding bivalves, the survival of Corbicula depends heavily on the abundance of some phytoplankton species (Sousa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental factors other than salinity may have shaped the colonization of clams during dispersal. High turbidity has the potential for decreased feeding, reduced reproduction and even to reduce shellfish survival (Avelar et al, 2014; Tuttle‐Raycraft & Ackerman, 2020; Wilber & Clarke, 2001). Besides, as filter‐feeding bivalves, the survival of Corbicula depends heavily on the abundance of some phytoplankton species (Sousa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is particularly relevant to lotic systems, which are inherently dynamic across temporal and spatial scales. A study conducted by Tuttle‐Raycraft & Ackerman (2020), examining the extent to which phenotypic plasticity develops in unionid species and consequently governs behavioural responses and physiological function, found that clearance rates of juveniles of the same species from the same source population, reared in different conditions, respond differently to the same stressor (Tuttle‐Raycraft & Ackerman, 2020). These differences are likely to be driven by local adaptations in gill structure (Vanden Byllaardt & Ackerman, 2014), such as gill surfaces that are more dense and larger palp structures (Tuttle‐Raycraft & Ackerman, 2019), representative of the prevailing hydrogeomorphological conditions (Silverman et al, 1997; Dutertre et al, 2009; Troost et al, 2009; Ouellette‐Plante et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should examine the phenotypic plasticity in locomotion behaviour, building upon explorations of plasticity in feeding behaviour (Tuttle‐Raycraft & Ackerman, 2020). Alterations in flow regime within juvenile rearing facilities could be used to examine whether a divergence in locomotion behaviour develops within juveniles sampled from the same population.…”
Section: Discussionmentioning
confidence: 99%